1998
DOI: 10.1103/physrevlett.81.1622
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Conductivity of the Classical Electron One-Component Plasma

Abstract: We carried out molecular dynamics experiments to determine the reduced heat diffusion coefficient D ‫ء‬ th and the reduced thermal conductivity l ‫ء‬ of the three-dimensional classical electron one-component plasma, for the 1 # G # 20 range of the plasma coupling parameter G. In our simulations the temperature of the system was spatially modulated, and D ‫ء‬ th and l ‫ء‬ were calculated from the relaxation time of the temperature profile. D ‫ء‬ th was found to decrease with increasing G, while l ‫ء‬ decreased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
1

Year Published

1999
1999
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 23 publications
3
25
1
Order By: Relevance
“…In the line of previous works [68][69][70][71][72][73], we investigate the transport properties of a one-component plasma via its dynamical structure factors. Since the scope of this paper is to study and compare transport in low-dimensional models, we limit ourselves to consider only one-dimensional plasmas in a static neutralizing background.…”
Section: B Numerical Simulations and Resultsmentioning
confidence: 99%
“…In the line of previous works [68][69][70][71][72][73], we investigate the transport properties of a one-component plasma via its dynamical structure factors. Since the scope of this paper is to study and compare transport in low-dimensional models, we limit ourselves to consider only one-dimensional plasmas in a static neutralizing background.…”
Section: B Numerical Simulations and Resultsmentioning
confidence: 99%
“…Large-scale molecular dynamics and Monte Carlo simulations of the OCP [47][48][49][50][51][52] have demonstrated that many of the basic properties such as diffusion and viscosity can be represented in terms of a single quantity, the plasma coupling coefficient Γ, defined by the ratio of the potential to kinetic energy,…”
Section: Inferno/ocp Modelmentioning
confidence: 99%
“…In practice, strong coupling directly influences the value of transport coefficients such as diffusion [4,5], shear viscosity [6,7], and thermal conductivity [8][9][10]. The lack of accurate transport coefficients often presents a key uncertainty when modeling plasmas that can reach strong coupling regimes, such as hydrodynamic simulations of dense plasmas encountered in the implosion of inertial confinement fusion (ICF) targets.…”
Section: Introductionmentioning
confidence: 99%